Domesticating the Beast: A "Resource Profile" Framework of Power Relations in Nonprofit–Business Collaboration. (December 2019) - Bouchard, Mathieu; Raufflet, Emmanuel
Researchers have addressed the implications of power imbalance for nonprofits engaging in collaborations with businesses. Yet as nonprofit–business collaboration intensifies, nonprofit managers' perceptions of power asymmetry in these relationships remain scantly studied. We argue that investigating these perceptions can sharpen the understanding of determinants and processes of power relations from a nonprofit perspective. To do so, we studied nonprofit–business collaboration in a network of international cooperation nongovernmental organizations (NGOs). Based on our findings, we designed a nonprofit-centric "resource profile" framework of power relations in cross-sector collaborations. This framework provides an empirically grounded tool to inform nonprofit managers' decision making as they engage in collaborations with businesses. Based on this framework, we elaborate a set of theoretical propositions to integrate existing knowledge and guide further nonprofit-centric research on power dynamics in cross-sector collaboration.